070 Do patients in congestive cardiac failure undergoing cardiac surgery demonstrate worse outcome compared to those recovered from a recent cardiac failure?. (22nd September 2015) - Attaran, S; Shaw, M; Bond, L; Pullan, DM; Fabri, BM
Abstract : Objectives: Cardiac surgery in patients with congestive cardiac failure (CCF) carries a significant risk of mortality and morbidity. Except for emergencies and in unstable cases, it has been recommended to delay the operation until the patient is fully recovered. The objective of this study was to determine the consequences of cardiac surgery in patients with current CCF undergoing surgery, and compare their outcome with the results of the operation in patients with a previous history of CCF. Methods: We have compared the outcome of patients who had CCF (n=707) at the time of cardiac surgery (Valve replacement or CABG), with those who had a previous history of CCF (n=1581) but recovered prior to their operation. The EuroScore was significantly higher in CCF patients (p<0.001). Impaired renal function was also more commonly observed in the patients with CCF (p<0.001). After adjusting for the pre-operative characteristics, the post-operative complications, post-operative CK-MB and in-hospital mortality were compared between the two groups. Results: Prior to adjusting for the pre-operative characteristics, in-hospital mortality (15.5%), post-operative complications, such as arrhythmias (31%), renal failure (19%), stroke (4.7%) and myocardial infarction (3%) were significantly higher in the CCF group compared to those with a previous CCF (Abstract 70 Table 1 ). When matched for the pre-operative characteristics, post-operative MI and arrhythmia were the main complications that were found to be significantly higher in current CCF group (Abstract 70 Table 2 ), but in-hospital mortality was not significantly different between the two groups. In addition, the results were not affected by the type of the procedure (valve or CABG). The main factor influencing post-operative mortality was EuroScore of the patient. Conclusion: Despite the significant risk of morbidity and mortality in patients with current CCF, cardiac operation to treat the cause should not be delayed, as this may lead to further deterioration of patient's condition. However, other risk factors should be taken into consideration for each individual. In other words, CCF should not be the main factor for postponing or denying a cardiac operation.